2019
DOI: 10.1111/vsu.13266
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical comparison of three epitendinous suture patterns as adjuncts to a core locking loop suture for repair of canine flexor tendon injuries

Abstract: Objective To determine the effects of different epitendinous sutures (ES) in addition to core locking‐loop (LL) sutures on the mechanical properties and gap formation in a canine cadaveric tendon model. Study design Experimental, ex vivo, biomechanical study. Sample population Seventy‐two cadaveric superficial digital flexor tendon specimens. Methods Superficial digital flexor tendon specimens were divided into four groups (n = 18): sharply transected and repaired with LL, LL + simple continuous ES, LL + Silfv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(75 citation statements)
references
References 41 publications
7
68
0
Order By: Relevance
“…An a priori power analysis was performed after completion of a pilot study using three dogs (six tendons). Based upon the failure load of previous ex vivo studies 18,19 and pilot testing conducted prior to definitive testing, a sample size calculation determined that ≥11 dogs per group would provide at least 90% power to detect a mean difference between groups of 30 ± 6 N at a 95% confidence level among independent measure. Pilot data were excluded from inclusion in the final statistical analysis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…An a priori power analysis was performed after completion of a pilot study using three dogs (six tendons). Based upon the failure load of previous ex vivo studies 18,19 and pilot testing conducted prior to definitive testing, a sample size calculation determined that ≥11 dogs per group would provide at least 90% power to detect a mean difference between groups of 30 ± 6 N at a 95% confidence level among independent measure. Pilot data were excluded from inclusion in the final statistical analysis.…”
Section: Discussionmentioning
confidence: 99%
“…3 Repairs with gaps >3 mm pose a greater risk for rerupture at the surgical site. 3 Researchers have demonstrated that ES use decreases the occurrence of gap formation to both 1-mm and 3-mm 18,19,34 while simultaneously increasing the tensile forces required to cause gapping between tendon ends. 26 In agreement with prior studies, use of a complete circumferential ES in groups 2 and 3 required ≈80% and 120% greater force to cause 1-mm and 3-mm gaps, respectively, compared with use of a partial circumferential ES repair alone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Epitendinous suture patterns improve biomechanical strength of the repair, minimize tendon gapping, and reduce the cross‐sectional area of the repaired tendon . In one study, the addition of an epitendinous suture decreased the rate of reoperation because of failure of the primary repair by 84% . Identification of novel tenorrhaphy techniques to resist gap formation at physiologic loads is a essential step in determining the efficacy and safety of surgical sutures in tendon repair prior to clinical use in dogs.…”
Section: Introductionmentioning
confidence: 99%